Prevalence and characteristics of transthyretin amyloid cardiomyopathy in hypertrophic cardiomyopathy - Pablo Garcia‐Pavia; Thibaud Damy; Nicolas Piriou; Roberto Barriales‐Villa; Francesco Cappelli; Catherine Bahus; Carmen Munteanu; Denis Keohane; Pablo Mallaina; Perry Elliott; the TTRACK investigators (ESC Heart Failure)
Abstract Aims Recognition of transthyretin amyloid cardiomyopathy is increasing due to advances in cardiac imaging and diagnostic strategies, but questions remain regarding disease frequency and characteristics. We examined the prevalence and characteristics of transthyretin amyloid cardiomyopathy in older patients with hypertrophic cardiomyopathy of unascertained aetiology. Methods and results TTRACK was a multicentre, non‐interventional, cross‐sectional epidemiologic study funded by Pfizer and conducted in 20 hospitals and medical centres in 11 countries (NCT03842163). Eligible patients were aged ≥50 years, had hypertrophic cardiomyopathy (maximal end‐diastolic left ventricular wall thickness ≥15 mm on echocardiogram) without an identified genetic or alternative origin at study enrolment, and underwent 99mTechnetium bone scintigraphy, with or without single photon emission computed tomography (SPECT). Cardiac‐versus‐bone uptake on scans was visually scored from 0 to 3 (Perugini scoring). Patients with grades 1–3 underwent monoclonal protein and laboratory testing and transthyretin (TTR) gene sequencing. Of 766 eligible patients, 691 (90.2%) had scintigraphy alone and 75 (9.8%) scintigraphy plus SPECT. Two hundred and eight patients (27.2%) had grade 2 or 3 cardiac uptake on scintigraphy; 144 (18.8%) had grade 2 or 3 cardiac uptake and no evidence of plasma cell dyscrasia and were diagnosed with transthyretin amyloid cardiomyopathy. Of patients with transthyretin amyloid cardiomyopathy, 11 (7.6%) had a pathogenic TTR gene variant and 34 (23.8%), 74 (51.7%), and 35 (24.5%) had New York Heart Association class I, II, and III/IV heart failure (HF) symptoms, respectively. Clinical and laboratory diagnostic characteristics were observed in ≥90% of patients with transthyretin amyloid cardiomyopathy. The characteristics most strongly associated with transthyretin amyloid cardiomyopathy on multivariable analysis were carpal tunnel syndrome (odds ratio [OR] 54.3; P < 0.0001) and male sex (OR 7.9; P < 0.0001). Conclusions In the TTRACK study, almost one in five patients ≥50 years of age with hypertrophic cardiomyopathy had transthyretin amyloid cardiomyopathy. Greater awareness of the frequency and characteristics of transthyretin amyloid cardiomyopathy in older patients with hypertrophic cardiomyopathy are needed to help improve early detection of this debilitating but treatable disease.